The Impact of Climate Change on Supply Chain Management - Narayan, Neetan (International Journal of Supply Chain and Logistics, 2025)
Purpose: This study examines the impact of climate change on global supply chain management by analyzing the influence of climate-related variables, specifically CO₂ emissions, temperature fluctuations, and flood-related economic damages, on key logistics performance indicators. These indicators include the customs score, infrastructure score, logistics performance index, and logistics competence and quality score. Methodology: A mixed-methods analytical approach was employed, incorporating regression analysis, correlation matrix evaluation, and principal components analysis (PCA), supplemented by visual analytics. This methodology enabled the identification of relationships between selected climate variables and supply chain performance metrics across various countries. Findings: The study reveals a statistically significant positive association between CO₂ emissions and improved logistics performance indicators. This suggests that regions with higher industrial output and consequently higher emissions often have more advanced logistics infrastructure and trade efficiency. Conversely, while flood-related economic damages exhibited a negative correlation with logistics performance, the relationship lacked statistical significance. The findings underscore the complex dynamic between industrial growth, environmental impact, and logistics efficiency. Unique Contribution to Theory, Practice, and Policy (Recommendations): This research contributes to the theoretical discourse by highlighting the dual role of industrial activity in enhancing logistics performance while exacerbating environmental degradation. Practically, it calls for urgent investment in climate-resilient infrastructure and adaptive logistics strategies. From a policy perspective, the study advocates for integrated climate and trade policies that align economic development with environmental sustainability. Future research should explore indirect and long-term effects of climate change on supply chains to inform more robust mitigation strategies.